(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article deals with the issue of introducing information and communication technologies in the educational process of teaching Russian as a foreign language with a focus on the combination of traditional and innovative methods. Innovative approaches including multimedia, cloud technologies and distance learning are analysed.